(3fRgI GdCHUGQ aj NhGU GdCMLGQs ((3eMehO UObi GdfSGN s)
(3ChdgG (B:s
(3hHYO agPG cJGH hVYJg ai NhGU GdCMLGQ jMJGLg cd Pi dH djYQa s
(3BNQgG (B:s
(3eG cGf HehVY EdG gQH efg GdLf hGdhMT hSGFQ GdghGe hGddg CYde s
(3GdCMLGQ gfG gi GdCMLGQ GdcQjeIs
(3fbdgG GdfGSN Yf GdCUd GdeMahX HQhGb GdCJQGc HGdCRgQ GdTQja HQbe (B2905 (3WHs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdcjejGA h GdWHjYjGJs